O Team Manager num Clube de Futebol - Diogo José Pinto Correia (2024)
This report concerns the professional internship work developed within the scope of the 2nd year of the 2nd cycle in Sports Management and was prepared with the aim of obtaining a Master's degree in Sports Management, by the Faculty of Sports of the University of Porto (FADEUP). The professional internship was carried out at Gondomar Sport Clube, more specifically in the club's B senior team. It took place between July 2023 and April 2024, lasting around 9 months. In terms of structure, the report is divided into five main chapters. The first chapter concerns the biographical framework, as well as the internship plan. The following chapter comprises a review of the literature on the areas of knowledge related to the activities that were carried out during the internship. Next, a description of the entity that hosted the internship is presented. Subsequently, all activities carried out in the internship are described. Chapter 5 presents a critical reflection on the development of the internship, as well as the skills acquired throughout the internship period. The report ends with the main conclusions and perspectives for the future. Through professional practice, theoretical knowledge was consolidated with the skills acquired and developed in the performance of Team Manager functions. This professional practice involved collaboration with the football department, in addition to all involvement in daily activities. Carrying out the internship and preparing this report was very important for the development of the intern's knowledge, who began to have a more concrete and systemic understanding of the activity of a Team Manager, as well as its importance in an organizational structure.